Pedagogy of Interiority as a Tool for Social-Emotional Education in the New Model of Public Education in Mexico: Scope and Limitations - Hilda Patiño Domínguez (European Scientific Journal, ESJ, 2019)
Based on the essential characteristics of the New Model for Public Education in Mexico, which will begin to operate in August 2018 throughout the country, this paper focuses on the introduction of social-emotional education in the curriculum of primary and secondary levels. It is, however, regarded as one of the most outstanding changes established in the Model. It offers a brief analysis of the theoretical-pedagogical principles of socialemotional education, as well as the main challenges that it would have to face to be implemented. The objective of this paper is to analyze the challenges posed by the implementation of socio-emotional education in the basic education curriculum in Mexico, specifically the one that implies the adoption of an adequate pedagogical approach. For this purpose, a comparative analysis was undertaken between the educational proposal of the model and the proposal of the Pedagogy of Interiority. This was carried out through the revision of the main categories of both approaches to detect their compatibility and complementarity. The analysis concludes that the Pedagogy of Interiority can contribute to a better appropriation and implementation of the proposal of Socio-Emotional Education in the Mexican Model.